Surviving Katrina : the Experiences of Low-Income African American Women - Pardee, Jessica Warner (FirstForumPress, Inc., 2014)
Jessica Pardee documents and examines the experiences of low-income African American women during Hurricane Katrina to uncover the ways that race, class, and gender shape the experiences of disasters. Drawing on intimate interviews to explore the complex challenges that these women faced in the course of the hurricane and its aftermath, Pardee reveals how, with so few material resources, they survived the storm and began the process of rebuilding their lives.